Sintomas de ansiedade e depressão: a remodelação psíquica na Insuficiência Cardíaca - Andréo, Juliana de Souza (2010)
Heart failure (HF) is a chronic disease that incapacitates and provokes emotional repercussions that may actually worsen the disease itself. Possible results include disinterest by the patient in pursuing treatment, increased hospitalization and reduced quality of life. The present study seeks to verify the presence of symptoms of anxiety and depression in patients with HF and compare them with a group of patients without HF for analysis in terms of principal socio demographic characteristics of the two groups. A total of 100 patients were evaluated. Fifty of these (the study group) had HF and 50 (the control group) without the disease. The presence of anxiety and depression were verified using three psychological instruments: Beck's Anxiety Inventory, Beck's Depression Inventory and the Hospital Scale of Anxiety and Depression. Patients were also submitted to a medical examination and responded to a socio demographic questionnaire. There was no significant difference between the two groups in terms of occupation, sex or number of children. The patients with HF demonstrated more anxiety and depression than the control group, as measured by all of the instruments. Further analysis revealed that the study group was older, had less leisure time and less education than the control group. The study thus revealed the importance of psychological instruments for the identification of symptoms of anxiety and depression among patients with HF. The need for psychological assistance, principally for upper working class patients was evident.